The inhibitory effects of antisense RNA on hepatitis B virus surface antigen synthesis. - Wu, J; Gerber, M A (Journal of General Virology, 1997)
Antisense RNA-mediated inhibition of gene expression has the potential for gene therapy of virus infections. We studied the inhibitory effect of antisense RNA directed against the hepatitis B virus (HBV) genome on the expression of the HBV surface antigen (HBsAg). Three prokaryotic antisense RNA expression constructs were produced which expressed antisense RNA complementary to the entire coding region (1.4 kb) and to 1.0 kb and 582 bp of the 5' region of HBsAg mRNA, respectively. In an in vitro translation system, all three antisense RNAs showed concentration-dependent inhibitory effects on translation of HBsAg mRNA. In a coupled in vitro transcription and translation system, concentration-dependent inhibition of HBsAg synthesis was observed for all above mentioned antisense RNAs. Three mammalian antisense RNA expression vectors were then constructed, expressing the same antisense RNAs as used above. Transfection of the vectors into Hep3B cells (an HBsAg secreting cell line) resulted in almost complete blockage of HBsAg production, whereas control vector transfected cells secreted high levels of HBsAg. The inhibitory effect lasted for more than 10 months post-transfection. To examine the possible mechanism of the antisense RNA effect in the cell line, we measured HBV mRNA levels in the transfected cells and found that the mRNA levels in the antisense RNA expressing cells were much lower than those in the control cells. Therefore, in Hep3B cells, the antisense RNAs inhibited HBsAg synthesis, at least partially, through the reduction of HBV mRNA levels.